Application of the principal component analysis–cloud model in the assessment of the seismic stability of slopes - Li, Wei-Wei; Xue, Er-Wei; Gu, Xin-Bao; Yang, Chao; Zhao, Chao (Frontiers in Earth Science, 2024)
The seismic stability assessment of slopes is important for the evaluation of slope instability, so an accurate estimation of the seismic stability level of slopes is vital. However, many factors affect the seismic stability of slopes, and their instability has a certain fuzziness and randomness. The principal component analysis–cloud model is introduced at first to assess the seismic stability of slopes. Second, the index coefficients are calculated using the principal component analytical method. Then, the characteristic value of the normal cloud model is obtained based on the classification standards of different indexes, and the relevant evaluation model is established. The conclusions are drawn that the method is feasible for the accurate assessment of the seismic stability of slopes, and its accuracy is very high. So, the suggested model can be widely applied in many fields, and a new approach can be provided for the future seismic stability assessment of slopes.